Nacionalno preverjanje znanja iz slovenščine ob koncu tretjega obdobja osnovne šole - analiza - Cestnik, Mojca (Jezik in slovstvo, 2012)
The article presents an analysis of knowledge tests in the subject of the Slovene language in the ninth grade of primary school in the period 2002-2012, with a special focus on pupils' achievements in selected tasks involving non-literary and literary texts. It is establised that un-depth reading and deducation on the basis of the information obtained in the texts places high demands on pupils, which demonstrates insufficient reading skills and points to the fact that the didactic process lacks independent production of written texts and argumentation based on the direct and indirect information in the texts. The test analysis has shown that the tasks are designed to assess the achievement of the majority of the goals and norms set by the Slovene primary school curriculum. As well as being important information for the individual pupil, teacher and school, data on pupils' achievements is also significant at the national level. On the basis of this data, it is possible to compensate for certain shortcomings in teaching Slovene, and to plan more efficient approaches in order to improve pupils' reading literacy.
Keywords: Slovene; slovenščina; umetnostno besedilo; neumetnostno besedilo; preverjanje znanja; nacionalno preverjanje; osnovna šola; primary school; 2002-2012